IN VITRO ANTIOXIDANT AND GLUCOSE UPTAKE EFFECT OF TRICHODESMA INDICUM IN L-6 CELL LINES - SUDHARSHAN REDDY DACHANI; SRINIVASA RAO AVANAPU; PRADEEP HULIKERE ANANTH (International Journal of Pharma and Bio Sciences, 2012)
The goal of the present study was to provide in vitro evidences for antioxidant and anti diabetic potential of Trichodesma indicum to generate a stronger biochemical rationale for further in vivo studies. The hydroalchohol extract of Trichodesma indicum whole plant was screened for its in vitro antioxidant activity using 2, 2-Diphenly 1-picryl hydrazyl assay, Scavenging of Nitric oxide and Superoxide radical methods, evaluation of Total antioxidant capacity of the extract and Reducing power assay. Cytotoxic effect of the extract was evaluated by MTT assay and in-vitro antidiabetic effect was studied using the glucose uptake model in rodent skeletal muscle cells (L-6 cells) involved in glucose utilization. The extract of Trichodesma indicum showed good antioxidant properties against 2, 2-Diphenly 1-picryl hydrazyl radical with low IC50 values 135mg/ml and against nitric oxide and superoxide radical exhibited poor scavenging properties with IC50 value of > 1000mg/ml. The total antioxidant activity which expressed equivalent to Ascorbic acid has 225.28 mg per gram of dried extract. The increased absorbance at 700 nm indicates an increase in reducing power of samples. The drug extract showed percentage growth inhibition value of 500 µg/ml and showed average glucose uptake (P<0.05) with percentage of glucose uptake of 91.03±10.12 over the control. The extract of Trichodesma indicum exhibited significant antioxidant activity and moderate antidiabetic activity and merits further investigation in animal models and support traditional claim.